The perceived benefits of choir involvement among vocal students in Music Faculty, Universiti Teknologi Mara / Jovenea Jim Lajim - Jim Lajim, Jovenea (Faculty of Music, 2010)
This study seeks to examine the perceived benefits of choir singing involvement and the student's perception of the importance of choir class as one of the subject in Universiti Teknologi MARA, Faculty of Music. Respondents for this study were Diploma program which were in semester 3 to semester 6 (n=26), and Degree program in education (n=13), performance (n=10) and composition (n-1). The overall results of the study shows that majority of the vocal student's perceived benefits which are the musical, physical, social and emotional in choir singing involvement. Majority of vocal students also agreed that the essential benefits in choir singing are the musical benefits, followed by physical, social and emotional. Majority of the respondents from diploma and degree program agreed that choir class is important. The study had been identified the perceptions of the importance of choir class among diploma and degree program, which are it helps to improved vocal technique, improved voice projection and improved singing in harmony.